Cybernetic analysis of the phenomenon of life - Bielecki, Andrzej (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2016)
In this paper the life phenomenon is analysed from cybernetic point of view. The Korzeniewski’s approach is discussed and complemented. The analysis is based on autonomous systems theory and information metabolism theory. Philosophical aspects of the problem are taken into consideration as well.